Analysis And Design Of Data Center Environmental Design In Pt. Medco Energi Using Tia-942 Standard With Ppdioo Life-cycle Approach - Azkya Telisha Hartono; Avon Budiyono; Ahmad Almaarif (eProceedings of Engineering, 2019)
Abstract The object of this research is an energy and power supply company named PT. Medco Energi. In this company, data center plays a role to help the business in the daily operations. With the rapid increase in the capacity and size of data center, there is a continuous increase in the demand for energy consumption, and also a lot of dangerous contaminants are threatening the environment. To overcome this problem, this research focuses on analyzing the current condition of data center and designing an improvement for the data center in PT. Medco Energi in terms of environmental design so that the design of the data center meets the criteria for environmental consideration in accordance with existing international standards and increase the value of the company. The standard that is used in this research is Telecommunications Industry Association (TIA) responded with the TIA942. This research used PPDIOO life-cycle as the methodology to prepare, plan and design the recommendation for environmental design of data center. The result of this research is a recommendation for improvement to PT. Medco Energi to help reducing energy costs and build an environmentally friendly data center design by implementing the parameters of environmental design in TIA-942 and achieving tier IV. Keywords: Data Center, TIA-942, Environmental Design, PPDIOO Lifecycle Abstrak Objek penelitian ini adalah perusahaan penyedia energi dan listrik bernama PT. Medco Energi. Di perusahaan ini, pusat data berperan untuk membantu bisnis dalam operasi sehari-hari. Dengan peningkatan yang cepat dalam kapasitas dan ukuran pusat data, mangka permintaan konsumsi energi pada pusat data juga meningkat, dan juga banyaknya kontaminan berbahaya yang mengancam lingkungan. Untuk mengatasi masalah ini, penelitian ini berfokus pada menganalisis dan merancang perbaikan untuk pusat data saat ini di PT. Medco Energi dalam hal desain lingkungan sehingga desain pusat data memenuhi kriteria untuk pertimbangan lingkungan sesuai dengan standar internasional yang ada dan meningkatkan nilai perusahaan. Standar yang digunakan dalam penelitian ini adalah Telecommunications Industry Association (TIA)-942. Penelitian ini menggunakan siklus hidup PPDIOO sebagai metodologi untuk menyiapkan, merencanakan dan merancang rekomendasi untuk desain lingkungan pusat data. Hasil penelitian ini merupakan sebuah rekomendasi untuk perbaikan PT. Medco Energi untuk membantu mengurangi biaya energi dan membangun desain pusat data yang ramah lingkungan dengan menerapkan parameter desain lingkungan di TIA-942 dan mencapai tingkat IV. Kata Kunci: Pusat Data, TIA-942, Desain Lingkungan, Siklus Hidup PPDIOO